Proposed new interior design of Land Rover Showroom for Land Rover Malaysia at Lot 51, Jalan Tun Abd Razak, Ipoh. / Mohamad Jazuli Jaafar - Jaafar, Mohamad Jazuli (Faculty of Architecture, Planning and Surveying, 2012)
This project is about Proposed New Interior Design of Land Rover Showroom For Land Rover Malaysia at Lot 51, Jalan Tun Abd Razak, Ipoh. Perak. Land Rover is a British car manufacturer and the second oldest four-wheel-drive car brand in the world (after Jeep). Land Rover was open their own showroom fifteen years ago. The client of this project is their marketing and PR manager, Mr. Andrew Wong. The reason to proposed this project is because the client decided to widen its business outride Kuala Lum0ur, preferably those of tourist attraction cities espacially north Malaysia like Ipoh, Perak. Ipoh was choose after had done survey and It seems that site is suitable for this project. The objective is to create a very well showroom with comfort and style with a good price related and attract more customers either from north Malaysia to the area has been choosen. With this project north Malaysians do not have to come to Kuala Lumpur to see the new luxury four-wheel-drive car, Land Rover. The target market for the customers of this showroom is for Malaysian who live at north Malaysia.